New prognostic model in patients with advanced urothelial carcinoma treated with second-line immune checkpoint inhibitors - Ernest Choy; Yohann Loriot; Fabio Calabrò; Cora N Sternberg; Guillermo De Velasco; Daniel Castellano; Roubini Zakopoulou; Aristotelis Bamias; Nicholas James; Axel Merseburger; F Lopez-Rios; Mario Kramer; et al. (Journal for ImmunoTherapy of Cancer)
Background Bellmunt Risk Score, based on Eastern Cooperative Oncology Group (ECOG) performance status (PS), hemoglobin levels and presence of liver metastases, is the most established prognostic algorithm for patients with advanced urothelial cancer (aUC) progressing after platinum-based chemotherapy. Nevertheless, existing algorithms may not be sufficient following the introduction of immunotherapy. Our aim was to develop an improved prognostic model in patients receiving second-line atezolizumab for aUC.Methods Patients with aUC progressing after cisplatin/carboplatin-based chemotherapy and enrolled in the prospective, single-arm, phase IIIb SAUL study were included in this analysis. Patients were treated with 3-weekly atezolizumab 1200 mg intravenously. The development and internal validation of a prognostic model for overall survival (OS) was performed using Cox regression analyses, bootstrapping methods and calibration.Results In 936 patients, ECOG PS, alkaline phosphatase, hemoglobin, neutrophil-to-lymphocyte ratio, liver metastases, bone metastases and time from last chemotherapy were identified as independent prognostic factors. In a 4-tier model, median OS for patients with 0–1, 2, 3–4 and 5–7 risk factors was 18.6, 10.4, 4.8 and 2.1 months, respectively. Compared with Bellmunt Risk Score, this model provided enhanced prognostic separation, with a c-index of 0.725 vs 0.685 and increment in c-statistic of 0.04 (p<0.001). Inclusion of PD-L1 expression did not improve the model.Conclusions We developed and internally validated a prognostic model for patients with aUC receiving postplatinum immunotherapy. This model represents an improvement over the Bellmunt algorithm and could aid selection of patients with aUC for second-line immunotherapy.Trial registration number NCT02928406.